THE INFLUENCE OF THE MENOPAUSE ON WORK PROCESSES AMONG HEALTH PROFESSIONALS IN A PUBLIC UNIVERSITY HOSPITAL - Lúcia Margarete dos Reis; Aline Loiola Moura; Maria do Carmo Lourenço Haddad; Marli Terezinha Oliveira Vannuchi; Francieli Nogueira Smanioto (Universidade Federal do Paraná, 2011)
A descriptive, quantitative study whose objective was to identify symptoms of the menopause and their interference in work processes. A stratified sample of 385 health professionals from a public university hospital was used; the data were collected via a socio-demographic questionnaire and the Woman's Health Questionnaire between March and May 2010, and were analysed with the help of statistical programmes after double-typing. Most commonly referred to, and with the biggest interference in work practices, were arthralgia and myalgia (76.6%) inferring in 27.5%; excessive tiredness and chronic headache (62.1%) interfering in 22.9% and 21.6% respectively. In the category of anxiety, agitation was referred to by 67% of health professionals, 24.4% stating that it can influence work processes. The preparation of women for the continuation of life after 40 should by a matter for public and institutional policy, promoting the health of the menopausal woman.